2006
DOI: 10.1172/jci26283
|View full text |Cite
|
Sign up to set email alerts
|

Mutual repression between steroid and xenobiotic receptor and NF- B signaling pathways links xenobiotic metabolism and inflammation

Abstract: While it has long been known that inflammation and infection reduce expression of hepatic cytochrome P450 (CYP) genes involved in xenobiotic metabolism and that exposure to xenobiotic chemicals can impair immune function, the molecular mechanisms underlying both of these phenomena have remained largely unknown. Here we show that activation of the nuclear steroid and xenobiotic receptor (SXR) by commonly used drugs in humans inhibits the activity of NF-κB, a key regulator of inflammation and the immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
340
1
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(362 citation statements)
references
References 64 publications
15
340
1
4
Order By: Relevance
“…[31][32][33] Consistently, IL-1a treatment in WT-derived hepatocytes enhanced NF-kB activation and reciprocally attenuated the expression of CYP1A2, CYP2E1, and CYP3A11, whereas IL-1ra had little effect on NF-kB activation and subsequent expression of these enzymes (Figure 4). In spite of the absence of significant differences in intrahepatic IL-1a and …”
Section: Reduced Susceptibility Of Il-1ra-deficient Hepatocytes To Apmentioning
confidence: 61%
See 1 more Smart Citation
“…[31][32][33] Consistently, IL-1a treatment in WT-derived hepatocytes enhanced NF-kB activation and reciprocally attenuated the expression of CYP1A2, CYP2E1, and CYP3A11, whereas IL-1ra had little effect on NF-kB activation and subsequent expression of these enzymes (Figure 4). In spite of the absence of significant differences in intrahepatic IL-1a and …”
Section: Reduced Susceptibility Of Il-1ra-deficient Hepatocytes To Apmentioning
confidence: 61%
“…57,58 Activated NF-kB can form a heterodimer with RXR, thereby antagonizing PXR/SXR-mediated signaling. 33,59 These molecular mechanisms may account for downregulation of CYP genes by IL-1 [42][43][44][45] and suppressed CYP1A2, CYP2E1, and CYP3A11 expression observed in IL-1ra KO mice, which is presumed to exhibit enhanced IL-1-mediated signals.…”
Section: Il-1ra and Apap-induced Liver Injury T Ishibe Et Almentioning
confidence: 99%
“…For example, our recent results suggest that PXR is important in preventing carcinogen-induced DNA damages (Naspinski et al, 2008). We and others have found cross talk between PXR-regulated pathway and NF-kB-regulated pathways (Gu et al, 2006;Zhou et al, 2006). These interactions create a 'checks and balances' relationship between pathways, which may have a role in some pathological processes such as IBD, which is a significant cancer risk factor.…”
mentioning
confidence: 84%
“…These interactions create a 'checks and balances' relationship between pathways, which may have a role in some pathological processes such as IBD, which is a significant cancer risk factor. Indeed, it has been found that pxr-null mutant mice showed increased expression of NF-kB target genes and marked intestinal inflammation (Zhou et al, 2006) reminiscent of that seen in humans with inflammatory bowel diseases such as the celiac disease (Kagnoff, 2005). Consistent with this PXR-NF-kB mutual repressive cross talk, it has been observed that activation of PXR by the agonist pregnenolone-16a-carbonitrile (PCN) significantly reduced dextran sulphate sodium-induced IBD in mouse model (Shah et al, 2007).…”
mentioning
confidence: 85%
“…Interestingly, induction of prostaglandin endoperoxide H synthase-2 by TCDD in rat hepatocytes appears to be mediated by both the AhR and by the ability of TCDD to increase overall C/EBP levels. 352 The ability of nuclear receptors and NFκB signaling to mutually repress transcription mediated by these factors has been firmly established [353][354][355] To gain insight into how the AhR and NFκB may interact at gene promoters, it is useful to examine the nature of the cross talk between nuclear receptors and NFκB. Numerous nuclear receptors have been shown to interact with RelA/p50, including, GR, ER, PPARγ, AR, and PXR.…”
Section: Evidence For Ahr-mediated Repression Of Nfκb and Ap-1 Tmentioning
confidence: 99%